Strategi Memilih Traffic yang Sesuai dengan Bisnis Para Pedagang Pusat Grosir Bogor Merdeka - Efrita Norman; Abdul Husenudin; Enah Pahlawati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Today's society has used social media to shop to meet their daily needs, besides that most people use social media for business, namely a means of promoting their business. This online buying and selling system is certainly very easy for consumers to make buying and selling transactions. Community service activities are carried out using problem-solving methods with a method of delivering socialization, consolidation, as well as identification of sales turnover and choosing the right business traffic for each business. Based on the dedication that has been carried out, it can be concluded that the service activities have run smoothly and the traders have obtained added value in the form of knowledge from the IAI-N Laa Roiba Bogor service team. Furthermore, this activity is expected to be able to improve the ability of traders in increasing visitors to their online stores. The suggestions that can be recommended are the need for further assistance to traders regarding how to take advantage of social media in increasing sales. Furthermore, it is still necessary to provide training that is able to trigger the enthusiasm of traders to increase additional income in addition to being able to survive during the pandemic as well as to improve family welfare.